Overtime Work Dual Job Holding and Taxation - Anders Frederiksen; Ebbe Krogh Graversen; Nina Smith (Institute for the Study of Labor (IZA), 2001)
Traditionally, labour supply data do not include much information on hours and wages in secondary job or overtime work. In this paper, we estimate labour supply models based on survey information on hours and wages in overtime work and second job which is merged to detailed register information on income taxes, deductions, taxable income etc. We also allow for the effect of observed fixed costs in main occupation and unobserved fixed costs in second job, and a ?stigmatization effect? from unemployment. The estimated models follow a ?Hausman-approach?. The results indicate that the labour supply elasticities are highly sensitive to the inclusion of information on overtime work and secondary job and to the handling of fixed costs of work. The estimated elasticities are numerically larger when explicit information on overtime and second job work is taken into account compared to traditional labour supply models without explicit information on overtime pay and second job wages. However, when the model allows for stigmatization effects and unobserved fixed costs of work in second job, the resulting elasticities reduce considerably.
Keywords: C13; H24; C21; C24; J22; 330; Labour supply; dual job holding; overtime work; piecewise linear budget constraints; Arbeitsangebot; Überstunden; Nebentätigkeit; Verschuldungsrestriktion; Steuerbelastung; Elastizität; Schätzung; Dänemark